Pola Asuh Ibu dalam Kebersihan Organ Reproduksi selama Menstruasi pada Remaja Tunagrahita - Iken Nafikadini; Driya Paramarta (Jurnal Kesehatan, 2020)
Mentally retarded children are children who have limitations in intellectual abilities. The classification of mental retardation based on intellectual classification is divided into three classes, namely debil/moron, moderate, and idiot. Mentally retarded children will step into adolescence which will be marked by physical changes but not in line with their thinking abilities. Reproductive health problems arise in children with mental retardation, especially during menstruation. Personal hygiene during menstruation should be noticed by mentally disabled children that have mental retardation. The role of mothers in caring is very helpful in personal hygiene during menstruation so that children with mental disabilities can be more independent and do not depend on others. The purpose of this study is to explore the mother education system  toward personal hygiene of reproductive organs during menstruation in mentally retarded adolescents. The determination of informants in this study by using purposive technique. Researchers collected data using in-depth interviews, and triangulation of sources. The results of this study indicate that all informants provided regulatory aspects through communicated oral regulations such as by reminding and giving examples. Most mothers have given punishment through verbal, such as yelling, and through physical punishment such as hitting. All mothers have given appreciation through praise in subtle ways, smiles, seduction when the child can behave following what has been taught. All  mothers have provided an aspect of consistency by reminding their children all the time, communicating with the school’s teacher, additionally providing examples and direct practice in front of the children.